Comprehensive review of melatonin as a promising nutritional and nutraceutical supplement - Waad W. Kamfar; Husam M. Khraiwesh; Mohammed O. Ibrahim; Alaa H. Qadhi; Wedad F. Azhar; Khloud J. Ghafouri; Maha H. Alhussain; Abdullah F. Aldairi; Abdullah M. AlShahrani; Abdullah F. Alghannam; Rwaa H. Abdulal; Abed H. Al-Slaihat; et al. (Heliyon, 2024)
Background: Melatonin is an indoleamine hormone secreted by the pineal gland at night and has an essential role in regulating human circadian rhythms (the internal 24-h clock) and sleep-wake patterns. However, it has recently gained considerable attention for its demonstrated ability in disease management. This review discusses the major biological activities of melatonin, its metabolites as nutritional supplements, and its bioavailability in food sources. Methods: The information acquisition process involved conducting a comprehensive search across academic databases including PubMed, Scopus, Wiley, Embase, and Springer using relevant keywords. Only the most recent, peer-reviewed articles published in the English language were considered for inclusion. Results: The molecular mechanisms by which melatonin induces its therapeutic effects have been the subject of various studies. Conclusion: While melatonin was initially understood to only regulate circadian rhythms, recent studies indicate that it has a far-reaching effect on various organs and physiological systems, such as immunity, cardiovascular function, antioxidant defense, and lipid hemostasis. As a potent antioxidant, anti-cancer, anti-inflammatory, and immunoregulatory agent, multiple therapeutic applications have been proposed for melatonin.